Hubungan Motivasi Diri Dengan Kepatuhan Diet Pada Penderita Diabetes Melitus Tipe 2 - Yuniari, Ni Kadek Yuniari (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic disease that requires long-term management, one of which is adherence to dietary recommendations. Poor dietary adherence remains a major problem among patients with T2DM. One important internal factor influencing dietary adherence is self-motivation, which encourages individuals to consistently engage in healthy behaviors. This study aims to determine the relationship between self-motivation and dietary adherence among patients with Type 2 Diabetes Mellitus. Methods: This study used a quantitative approach with a cross-sectional design. The study population consisted of 95 respondents, with 40% aged over 56 years. Data were collected using a self-motivation questionnaire and a dietary adherence questionnaire. Results: The results showed that most respondents had a good level of self-motivation, with 64 respondents (67.4%), and a moderate to good level of dietary adherence, with 68 respondents (71.6%). The Spearman rank correlation test showed a correlation coefficient (r) of 0.504 with a significance value (p-value) of 0.000 (p < 0.01). Conclusion: Self-motivation plays an important role in encouraging patients with Type 2 Diabetes Mellitus to adhere to the recommended diet.